The Firebrand: Clay Center, Clay County, Kansas, Dec. 1893 – Nov., 1894 - Collins, Becky (Kansas State University. Dept. of History, 2011)
Among the 713 newspapers in print in Kansas in the 1880s, a single short-lived newspaper provides insight into political shifts and battles in small towns. The Firebrand newspaper in Clay Center provided inflammatory rhetoric for a single year, also switching political sides from Republican to Democrat. This is an in-depth study of one newspaper; the author, a journalism major, read every issue and perceptively analyzes tone, message, and content.
Keywords: Clay County; Clay Center; Early newspapers; Republican Party; Journalism